Pengaruh Implementasi Kebijakan Upah Minimum pada Hubungan Kerja Perusahaan dengan Pekerja di Kabupaten Bandung - Makasau, Muslimin Muhammad Andi (Jurnal Ilmu Administrasi Negara, 2009)
The main problem in this research is that “the implementation of the public policy aboutRegency Minimum Wages in Kabupaten Bandung isn’t yet fully implementation in supportingindustrial relation between industries-workers”. Therefore, from the workers side the continue toeffort the implementation of the policy and to make the policy as base for workers payment asindustries remain unable to implement the policy and than become the problem industries-workers inKabupaten Bandung. The objective of research to measure influence of the Regency MinimumWages public policy on the workers relation. Population usearch are industries with category big,middle and little. Respondents consist of 110 people with using proportional random samplingmethods. The instrument of collecting data were questionnaire with using likert scale. The measure-ment uses the path analysis with the formula of statistical test based on the hypothesis to validatethe theory of the public policy implementation that consist of the Policy Content, the Policy Informa-tion, the Policy Support, and the Potency of the Policy Implementation. The result of researchanalysis shows that the content of Policy, the Policy Information, the Policy Support, and the PolicyPotency, have the influence on the workers relations between the industries and workers, which isstated in the value of multiple determination coefficient test from all variables. The research findingthat there are other aspect that must be added to complement the existing four requarment of theRegency Minimum Wages which are the aspects of justice, controlling and environment. Thereforeit is hoped that any requarment in the future could include theses seven requarment of the RMWpolicy implementation.